1999
DOI: 10.1074/jbc.274.15.9923
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Cyclooxygenase-related Prostaglandin Synthesis in Coral

Abstract: Certain corals are rich natural sources of prostaglandins, the metabolic origin of which has remained undefined. By analogy with the lipoxygenase/allene oxide synthase pathway to jasmonic acid in plants, the presence of (8R)-lipoxygenase and allene oxide synthase in the coral Plexaura homomalla In the present study, active preparations of G. fruticosa have been used to identify both types of arachidonic acid metabolism and specific inhibitors were used to establish the enzyme type involved in the prostaglandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…Knight et al, 1999) suggesting the existence of a COX-derived mechanism for PG biosynthesis. More recent biochemical studies using the Arctic coral Gersemia fruticosa have demonstrated that radiolabelled arachidonate can be converted to the unstable intermediate PGG 2 (Varvas et al, 1999). The cDNA that codes for a COX isozyme was subsequently cloned from this coral ) and the deduced amino acid sequence of the G. fruticosa COX revealed the presence of Ile 523 that mainly confers the specificity of this enzyme towards COX inhibitors.…”
Section: Prostanoid Biosynthetic Pathways In Invertebratesmentioning
confidence: 99%
“…Knight et al, 1999) suggesting the existence of a COX-derived mechanism for PG biosynthesis. More recent biochemical studies using the Arctic coral Gersemia fruticosa have demonstrated that radiolabelled arachidonate can be converted to the unstable intermediate PGG 2 (Varvas et al, 1999). The cDNA that codes for a COX isozyme was subsequently cloned from this coral ) and the deduced amino acid sequence of the G. fruticosa COX revealed the presence of Ile 523 that mainly confers the specificity of this enzyme towards COX inhibitors.…”
Section: Prostanoid Biosynthetic Pathways In Invertebratesmentioning
confidence: 99%
“…By analogy to the plant CYP74 P450 family that metabolize fatty acid hydroperoxides, such homologues could exhibit AOS, hydroperoxide lyase, epoxyalcohol synthase, or divinyl ether synthase activities (6). Whether residing in fusion proteins or as autonomous polypeptides, 8R-LOX and AOS activities are ubiquitous in corals (5,33,34), and their expression will likely be detected in other invertebrates (35). Other homologues of the AOS domain suggest expanded roles.…”
Section: The Chemical Nature Of the U-shaped Cavity Is Complementary mentioning
confidence: 99%
“…For a time, evidence from P. homomalla and other corals suggested that prostaglandin biosynthesis occurred analogously to jasmonic acid synthesis in plants via the lipoxygenase-allene oxide route (8,(10)(11)(12). Formation of an intermediate typical to mammalian prostaglandin synthesis in coral was established through our biochemical studies on the Arctic soft coral Gersemia fruticosa (13)(14)(15). This prostaglandin-containing coral converts radiolabeled arachidonic acid to the endoperoxide intermediate PGG 2 in vitro.…”
mentioning
confidence: 99%